Bursting the bubble on bacterial biofilms: a flow cell methodology - Crusz, Shanika A.; Popat, Roman; Rybtke, Morten Theil; Cámara, Miguel; Givskov, Michael; Tolker-Nielsen, Tim; Diggle, Stephen P.; Williams, Paul (Taylor & Francis, 2012)
The flow cell biofilm system is an important and widely used tool for the in vitro cultivation and evaluation of bacterial biofilms under hydrodynamic conditions of flow. This paper provides an introduction to the background and use of such systems, accompanied by a detailed guide to the assembly of the apparatus including the description of new modifications which enhance its performance. As such, this is an essential guide for the novice biofilm researcher as well as providing valuable trouble-shooting techniques for even the most experienced laboratories. The adoption of a common and reliable methodology amongst researchers would enable findings to be shared and replicated amongst the biofilm research community, with the overall aim of advancing understanding and management of these complex and widespread bacterial communities.